ANALISIS PENGARUH BAURAN PEMASARAN (7P) TERHADAP LOYALITAS PELANGGAN SERTA DAMPAKNYA PADA PROFITABILITAS SAHABAT LAUNDRY BANJARMASIN - Ryka Voish Elvido Silvia; Ni Nyoman Suarniki; Dewi Setiawati; Amilia Norjannah (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyse the influence of the marketing mix (7Ps) on customer loyalty and its impact on the profitability of Sahabat Laundry Banjarmasin. The service marketing mix, comprising product, price, place, promotion, people, process and physical evidence, plays a key role in creating value and customer experiences that ultimately foster loyalty. This study employs a mixed-methods approach, with a quantitative stage involving a questionnaire administered to 100 respondents and multiple linear regression analysis, and a qualitative stage involving the interpretation of the regression results in relation to monthly turnover data. The results indicate that, taken together, the marketing mix has a significant effect on customer loyalty; however, when analysed individually, only promotion, process and tangible evidence were found to be significant. Furthermore, customer loyalty contributes to profitability through increased transaction frequency, revenue stability, reduced customer acquisition costs, and the effectiveness of word-of-mouth. With a monthly turnover of Rp25–28 million, strengthening loyalty-based strategies is key to improving profit margins. This study confirms that customer loyalty is a strategic asset that must be built through the optimisation of marketing mix elements to support long-term profitability.